Plant and fungal collections: Current status, future perspectives. Issue 5 (29th September 2020) - Paton, Alan; Antonelli, Alexandre; Carine, Mark; Forzza, Rafaela Campostrini; Davies, Nina; Demissew, Sebsebe; Dröge, Gabriele; Fulcher, Tim; Grall, Aurelie; Holstein, Norbert; Jones, Meirion; Liu, Udayangani; et al.
Societal Impact Statement: Plant and fungal specimens provide the auditable evidence that a particular organism occurred at a particular place, and at a particular point in time, verifying past occurrence and distribution. They also document the aspects of human exploration and culture. Collectively specimens form a global asset with significant potential for new uses to help address societal and environmental challenges. Collections also serve as a platform to engage and educate a broad range of stakeholders from the academic to the public, strengthening engagement and understanding of plant and fungal diversity—the basis of life on Earth. Summary: We provide a global review of the current state of plant and fungal collections including herbaria and fungaria, botanic gardens, fungal culture collections, and biobanks. The review focuses on the numbers of collections, major taxonomic group and species level coverage, geographical representation and the extent to which the data from collections are digitally accessible. We identify the major gaps in these collections and in digital data. We also consider what collection types need to be further developed to support research, such as environmental DNA and cryopreservation of desiccation‐sensitive seeds. Around 31% of vascular plant species are represented in botanic gardens, and 17% of known fungal species are held in culture collections, both these living collections showing a bias toward northern temperate taxa. Only 21% of preserved collections are available via the Global Biodiversity Information Facility (GBIF) with Asia, central and north Africa and Amazonia being relatively under‐represented. Supporting long‐term collection facilities in biodiverse areas should be considered by governmental and international aid agencies, in addition to short‐term project funding. Institutions should consider how best to speed up digitization of collections and to disseminate all data via aggregators such as GBIF, which will greatly facilitate use, research, and community curation to improve quality. There needs to be greater alignment between biodiversity informatics initiatives and standards to allow more comprehensive analysis of collections data and to facilitate linkage of extended information, facilitating broader use. Much can be achieved with greater coordination through existing initiatives and strengthening relationships with users. Abstract : Plant and fungal specimens provide the auditable evidence that a particular organism occurred at a particular place, and at a particular point in time, verifying past occurrence and distribution. They also document the aspects of human exploration and culture. Collectively specimens form a global asset with significant potential for new uses to help address societal and environmental challenges. Collections also serve as a platform to engage and educate a broad range of stakeholders from the academic to the public, strengthening engagement and understanding of plant and fungal diversity—the basis of life on Earth.